1988
DOI: 10.1104/pp.88.2.383
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Leaf Nitrate Reductase Genes from Tomato and Tobacco in Relation to Light-Dark Regimes and Nitrate Supply

Abstract: The influence of light-dark cycles and nitrate supply on nitrate reductase (NR) mRNA levels was studied in two plant species, tobacco (Nicotiana tabacum) and tomato (Lycopersicon esculentum) using specific NR DNA probes. In the same series of experiments, changes in the levels of NR protein (NRP) by enzyme-linked immunosorbent assay and changes in the level of NADH-nitrate reductase activity (NRA) were also followed. During a light-dark cycle, it was found that in both tomato and tobacco, NR mRNA accumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
130
1
13

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(158 citation statements)
references
References 24 publications
14
130
1
13
Order By: Relevance
“…The decline in NR mRNA after peak accumulation in leaves and roots argues for a negative feedback control of NR mRNA synthesis and/or degradation in birch. Probably this reflects a general mechanism of NR regulation in plants, because similar changes of NR mRNA pools following the induction by nitrate were also found in herbaceous species (11,18). Although feedback regulation of NR by products of nitrate assimilation has been reported for fungi (21), the stimuli involved in plants are not known.…”
Section: Induction Of Nirmentioning
confidence: 99%
See 1 more Smart Citation
“…The decline in NR mRNA after peak accumulation in leaves and roots argues for a negative feedback control of NR mRNA synthesis and/or degradation in birch. Probably this reflects a general mechanism of NR regulation in plants, because similar changes of NR mRNA pools following the induction by nitrate were also found in herbaceous species (11,18). Although feedback regulation of NR by products of nitrate assimilation has been reported for fungi (21), the stimuli involved in plants are not known.…”
Section: Induction Of Nirmentioning
confidence: 99%
“…Upon transfer of ammonium-grown seedlings to a nitrate-containing medium, NR activities dramatically increased in leaves and roots of illuminated plants. This induction strictly depends on the presence of light, thus resembling the situation found for NADH-specific NR in herbaceous species (11,18,23 (11). This could not be tested in birch due to the lack of NR-specific antibodies.…”
Section: Induction Of Nirmentioning
confidence: 99%
“…On the other hand, several recent studies have demonstrated diurnal or circadian rhythmicity in the level of specific mRNAs (8,9,13,18,21,25,28 (6). Gels were prepared for fluorography using Amplify (Amersham, UK) and exposed to preflashed Kodak X-Omat AR film, 48 Leaves of S. alba were harvested and their mRNA analyzed at the beginning (0 h), middle (4 h), and end of the day (8 h) as well as three times during the following night (12,16, and 20 h).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Segundo Galangau et al (1988) e Vincentz et al (1993) a atividade da enzima RN nas folhas e raízes pode ser induzida pela presença do substrato…”
Section: Regulação Da Atividade Da Redutase Do Nitrato (Rn)unclassified
“…A luz e o teor de nitrato são fatores importantes na indução e manutenção da atividade da enzima RN nos tecidos vegetais (Hageman & Flesher, 1960;Beevers & Hageman, 1969;Galangau et al, 1988;Vincentz et al, 1993). De acordo com diversos autores a atividade da RN nas folhas de várias espécies, aumenta durante as horas de luz e decresce no escuro (Harper & Hageman, 1972;Lewis et al, 1982;Hipkin et al, 1984).…”
Section: Introductionunclassified